Reference intervals for serum 1, 5‐anhydroglucitol of a population with normal glucose tolerance in Jiangsu Province. Issue 6 (9th January 2020) - Chen, Cheng; Wang, Xiaohang; Tan, Yuanyuan; Yang, Jiao; Yuan, Yuexing; Chen, Juan; Guo, Haijian; Wang, Bei; Sun, Ziling; Wang, Yao
Abstract: Background: Serum 1, 5‐anhydroglucitol (1, 5‐AG) is a new glycemic marker which can reflect glucose fluctuation over 3 to 7 days and is now increasingly used to monitor glucose control and to screen for diabetes. However, 1, 5‐AG has not been widely used in China due to lack of epidemiological support. Our study aims to establish the reference intervals for a population with normal glucose tolerance in Jiangsu Province and to explore the determinants of these intervals. Method: The study enrolled 646 healthy adults aged 20 to 70 years in Jiangsu Province in 2018 after oral glucose tolerance test. 1, 5‐AG, fasting and 2‐hour glucose, UA, liver enzyme, serum lipid, creatinine, and glycosylated hemoglobin were measured. We calculated reference intervals using the parametric method and examined the relationship between 1, 5‐AG and influence factors. Results: The average age of the participants was 50.5 ± 9.0 years, and 69.5% of them were females. The reference intervals were 15.8 to 52.6 μg/mL for males and 14.3 to 48.0 μg/mL for females. Among females, the reference intervals were 13.9 to 45.3 and 14.6 to 49.6 μg/mL for menopausal and postmenopausal females, respectively. Males showed higher 1, 5‐AG concentrations than females, and postmenopausal females had higher 1, 5‐AG than menopausal females. There was a positive correlation between uric acid and 1, 5‐AG in both genders. Positive correlation between 1, 5‐AG and age was only observed in females. Conclusion: We established reference intervals for 1, 5‐AG in Jiangsu Province, and the level of 1, 5‐AG is affected by sex, uric acid, and age. Abstract : Highlights Males, menopausal females, and postmenopausal females had corresponding reference intervals for 1, 5‐anhydroglucitol (1, 5‐AG). Levels of serum uric acid and age should be taken into consideration when interpreting 1, 5‐AG. 摘要: 背景: 血清1, 5‐脱水葡萄糖醇(1, 5‐AG)是一种能反映3‐7天血糖波动的新指标, 近年来被广泛地运用于糖尿病监测和筛查中。但在中国仍因缺少1, 5‐AG相关流行病学研究而未广泛应用。本研究旨在建立中国江苏省糖耐量正常人群参考值范围以及影响因素。 方法: 本研究于2018年在江苏省招募年龄20‐70岁之间的成年人, 通过口服葡萄糖耐量试验, 纳入646名糖耐量正常的健康受试者。测量血1, 5‐AG值、空腹及餐后2小时血糖、尿酸、肝酶、血脂、肌酐及糖化血红蛋白等生化指标。运用参数法计算受试者血清1, 5‐AG值参考值范围, 并观察其与其他影响因素的关系。 结果: 本研究受试者年龄50.5±9.0岁, 女性占69.5%。1, 5‐AG参考值范围:男性为15.8‐52.6μg/mL；女性为14.3‐48.0μg/mL, 其中非绝经女性为13.9‐45.3μg/mL, 绝经女性为14.6‐49.6μg/mL。男性组1, 5‐AG值明显高于女性组, 绝经女性的1, 5‐AG水平高于非绝经女性。1, 5‐AG水平与尿酸水平在两性之间呈正相关关系。女性组1, 5‐AG与年龄呈正相关关系。 结论: 本研究在中国江苏省建立了1, 5‐AG参考值范围；1, 5‐AG值与性别及年龄和尿酸相关。